2012
DOI: 10.1371/journal.pone.0046501
|View full text |Cite
|
Sign up to set email alerts
|

Localising Loci underlying Complex Trait Variation Using Regional Genomic Relationship Mapping

Abstract: The limited proportion of complex trait variance identified in genome-wide association studies may reflect the limited power of single SNP analyses to detect either rare causative alleles or those of small effect. Motivated by studies that demonstrate that loci contributing to trait variation may contain a number of different alleles, we have developed an analytical approach termed Regional Genomic Relationship Mapping that, like linkage-based family methods, integrates variance contributed by founder gametes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
180
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(183 citation statements)
references
References 25 publications
2
180
1
Order By: Relevance
“…On the other hand, several exclusive regions reaching the suggestive level were identified only with RHM. Nagamine et al (2012) showed that RHM performed better than a standard GWA study, especially when associated SNPs do not have large enough effect to be declared significant at the genome-wide level. In principle, estimating the trait heritability for chosen regions allows integration of the variance contributed by both rare and common variants into a single estimate of additive variance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several exclusive regions reaching the suggestive level were identified only with RHM. Nagamine et al (2012) showed that RHM performed better than a standard GWA study, especially when associated SNPs do not have large enough effect to be declared significant at the genome-wide level. In principle, estimating the trait heritability for chosen regions allows integration of the variance contributed by both rare and common variants into a single estimate of additive variance.…”
Section: Discussionmentioning
confidence: 99%
“…Nagamine et al (2012) suggested that the use of smaller windows can improve mapping resolution. In our study, this was not always the case; that is, when moving from 100 to 50 SNP wide windows, only in a few cases, there was an improvement in the level of significancesometimes regions became not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the sequence kernel association test (SKAT) (Wu et al 2011) and multiple-SNP methods such as regional heritability mapping (RHM), a variance-component approach based on restricted maximum-likelihood (REML) estimation of additive variance explained by genomic regions of a given size (Nagamine et al 2012). A comparison of the power of these two methods and other composite P-value methods and single-SNP methods has been made recently by Uemoto et al (2013).…”
mentioning
confidence: 99%
“…Unfortunately, GWAS seems to localise a relatively small proportion of the total genetic variation in the traits of interest (e.g., Kemper et al, 2011). An alternate approach proposed by Nagamine et al (2011), known as Regional Genomic Relationship Mapping (RGRM), may better capture genetic effects. This method provides heritability estimates attributable to small genomic regions, and it has the power to detect regions containing multiple alleles that individually contribute too little variance to be detected by GWAS.…”
Section: Regional Genomic Relationship Mapping To Indentify Loci Undementioning
confidence: 99%